The effects of access block in the Emergency Department, Hospital Universiti Sains Malaysia - Nor, Wan Suzanne Wan Mohd (2017)
Background: Emergency Department(ED) is the hospital’s access door to inpatient treatment and management. Overcrowding and access block had been recognized as the major challenges in Emergency Department nowadays. Access block, or delays in admission of patients to hospital inpatient areas from ED, has been linked to increase the length of inpatient hospital stay, increase comorbidity and mortality as well as being the fundamental problem leading to ED overcrowding. This study is to determine the effects of access block in the ED specifically to the length of inpatient hospital stay and correlation with the patient’s mortality. Objective: To study the effects of access block in the Emergency Department, Hospital Universiti Sains Malaysia, Kubang Kerian. Methodology: A retrospective study was conducted in Emergency Department, Hospital Universiti Sains Malaysia, Kelantan between the period of June 2016 till August 2016 involving all patients registered at Emergency department. The data were obtained from Emergency Department registration record. Patient’s folders were reviewed to get further information pertaining to the study. The relationship between access block with the patient’s length of hospital stay and mortality were analyzed using comparative analysis and Logistic regression. Results: A total of 270 patients were recruited for the study. 104 patients (38.5%) were delayed to get the inpatient bed within the appropriate time frame which is more than 4 hours from the decision time of admission. Majority of these group (access block group), (74, 71.1%) were medical cases in comparison to surgical cases (30, 28.9%). Mean access block time in medical cases was 9 hours and 18 minutes while in surgical cases was 7 hours and 41 minutes. The mean length of hospital stay (LOS) in access block group was 6.35 days (95% CI=5.27 to 7.42 days), compared with 5.98 days (95% CI=4.56 to 7.40) in non access block group. For the mortality, there were 9 death in the access block and 3 in the non access block (3.6% and 1.2% respectively, P= 0.031).